Occupational exposure during emergency department thoracotomy: A prospective, multi-institution study. Issue 1 (July 2018) - Nunn, Andrew; Prakash, Priya; Inaba, Kenji; Escalante, Alvarez; Maher, Zoë; Yamaguchi, Seiji; Kim, Dennis Y.; Maciel, James; Chiu, William C.; Drumheller, Byron; Hazelton, Joshua P.; Mukherjee, Kaushik; et al.
Abstract : BACKGROUND: Occupational exposure is an important consideration during emergency department thoracotomy (EDT). While human immunodeficiency virus/hepatitis prevalence in trauma patients (0–16.8%) and occupational exposure rates during operative trauma procedures (1.9–18.0%) have been reported, exposure risk during EDT is unknown. We hypothesized that occupational exposure risk during EDT would be greater than other operative trauma procedures. METHODS: A prospective, observational study at 16 US trauma centers was performed (2015–2016). All bedside EDT resuscitation providers were surveyed with a standardized data collection tool and risk factors analyzed with respect to the primary end point, EDT occupational exposure (percutaneous injury, mucous membrane, open wound, or eye splash). Provider and patient variables and outcomes were evaluated with single and multivariable logistic regression analyses. RESULTS: One thousand three hundred sixty participants (23% attending, 59% trainee, 11% nurse, 7% other) were surveyed after 305 EDTs (gunshot wound, 68%; prehospital cardiopulmonary resuscitation, 57%; emergency department signs of life, 37%), of which 15 patients survived (13 neurologically intact) their hospitalization. Overall, 22 occupational exposures were documented, resulting in an exposure rate of 7.2% (95% confidence interval [CI], 4.7–10.5%) per EDT and 1.6% (95% CI, 1.0–2.4%) per participant. No differences in trauma center level, number of participants, or hours worked were identified. Providers with exposures were primarily trainees (68%) with percutaneous injuries (86%) during the thoracotomy (73%). Full precautions were utilized in only 46% of exposed providers, while multiple variable logistic regression determined that each personal protective equipment item utilized during EDT correlated with a 34% decreased risk of occupational exposure (odds ratio, 0.66; 95% CI, 0.48–0.91; p = 0.010). CONCLUSIONS: Our results suggest that the risk of occupational exposure should not deter providers from performing EDT. Despite the small risk of viral transmission, our data revealed practices that may place health care providers at unnecessary risk of occupational exposure. Regardless of the lifesaving nature of the procedure, improved universal precaution compliance with personal protective equipment is paramount and would further minimize occupational exposure risks during EDT. LEVEL OF EVIDENCE: Therapeutic/care management study, level III. Abstract : Supplemental digital content is available in the text.